Human Conventional and Plasmacytoid Dendritic Cells Differ in Their Ability to Respond to Saccharomyces cerevisiae - Sabatini, Andrea; Guerrera, Gisella; Corsetti, Marta; Ruocco, Gabriella; De Bardi, Marco; Renzi, Sonia; Cavalieri, Duccio; Battistini, Luca; Angelini, Daniela Francesca; Volpe, Elisabetta (Frontiers in Immunology, 2022)
Saccharomyces cerevisiae is a commensal yeast colonizer of mucosal surfaces, and an emerging opportunistic pathogen in the mucosa and bloodstream. The role of S. cerevisiae has been largely characterized in peripheral blood mononuclear cells and monocyte derived dendritic cells, where yeast cells induce production of inflammatory cytokines through the interaction with mannose receptors, chitin receptors, DC SIGN, and dectin1. However, the response of blood circulating dendritic cells (DCs) to S. cerevisiae has never been investigated. Among blood DCs, conventional DCs (cDCs) are producers of inflammatory cytokines, while plasmacytoid DCs (pDCs) are a specialized population producing large amount of interferon (IFN)-, which is involved in the antiviral immune response. Here, we report that both human DC subsets are able to sense S. cerevisiae. In particular, cDCs produce interleukin (IL)-6, express activation markers, and promotes T helper 17 cell polarization in response to yeasts, similarly behaving to monocyte derived DCs, previously described. Interestingly, pDCs, and not cDCs, sense fungal nucleic acids, leading to the generation of P1-pDCs (PD-L1+CD80–), a pDC subset characterized by the production of IFN- and the induction of a Th profile producing IL-10. These results highlight a novel role of pDCs in response to S.cerevisiae, that could be important for the regulation of the host microbiota-immune system balance, and of anti-fungal immune response.